“Estrategias colaborativas en el proceso educativo” - Guerra Haro, Karina Elizabeth (2022)
The current reseaech had as purpose to demonstrate the collaborative strategies incidence in the Social Studies area, having as the aim of improving the teaching-learning process, which it was applied the qualitative approach, whit the students and teachers participation of basic education fifth year, from “Alejandro Dávalos Calle” Educational Unit. It was used observation and interview techniques, with their respective instruments; interview guide and observation guide, to identify the problems, what they have teachers have in the innovative activity´s implementation, which strengthen students´ critical-reflective thinking. In this sense, the results show, what when making team activities, they feel more motivated and interested, improving interpersonal relationships, contributing with their individual knowledge and skills, also, it is evidenced, which with a teacher good didactic process, the student can reach a understanding of topic global. Therefore, the elaboration of the collaborative strategies guide, which are: essay strategies, critical thinking strategy, elaboration and organization strategy and finally, the puzzle strategy; they improved communication between teacher-student , elimminating the traditional clases lags, helping to promote the significant knowledge construction.